Tendency and Student Satisfaction Using Printed and Electronic Information Resources at the University of North Sumatra Library - Santana Sembiring; Jonner Hasugian (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the study: The presence of electronic Information Resources (SDI) in university libraries is especially attractive for users. The convenience and not having to come physically to the location make users prefer to use electronic SDI compared to printed SDI. Purpose: The main purpose of this research is to find out the trend of using SDI in the USU Library based on the field of science. Another objective is to find out the actual satisfaction of users with the electronic and printed SDI available at the USU Library. Method: This research is descriptive. The method used is a survey and data collection techniques are carried out by distributing questionnaires to respondents. Findings: The results showed that USU undergraduate students (S1) had different tendencies in using information resources. Students from non-exact study programs prefer to use the printed format, while students from the exact sciences study program more often use electronic SDI. Then in terms of the satisfaction that is desired and obtained, non-exact students have an average percentage value that is higher than exact. Conclusion: The results of this study can be used as evaluation material for the USU Library to continue to provide SDI in both printed and electronic formats following the information needs of its users.